The Role of GPUs in Accelerating Machine Learning Workloads - Rajeev Reddy Chevuri (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents a comprehensive overview of Graphics Processing Units (GPUs) and their transformative role in accelerating machine learning workloads. Starting with an explanation of the fundamental architectural differences between GPUs and CPUs, the article explores how the parallel processing capabilities of GPUs enable dramatic improvements in training deep learning models. The discussion covers GPU applications across convolutional neural networks, transformer architectures, and multi-GPU training strategies. Beyond training, the article examines GPU acceleration in inference, scientific computing, data preprocessing, and emerging application domains. Cost-effective deployment strategies are also addressed, including cloud versus on-premises considerations, container orchestration, dynamic resource allocation, and computational optimization techniques. Throughout, the article highlights how GPUs have fundamentally altered what is computationally feasible in artificial intelligence, enabling complex models and applications that would otherwise remain theoretical.